Targeted advertising and costly consumer search. (6th November 2022) - Burguet, Roberto; Petrikaitė, Vaiva
Abstract: We study targeting of advertising based on information about the consumer's likely ranking of products. Firms send ads to more promising consumers. Thus, targeting increases the expected willingness to pay for the product the consumer learns about but also reduces the expected differentiation of these products. The two effects push search, and so prices, in opposite direction. The first effect is more important for lower search costs. The second is stronger the larger the number of products. The improved selection under targeting increases firms' profitability and so advertising effort.